Shedding light on Piper’s identity via computational mass spectrometry - Osman, Muhamad Faris; Mohd Faudzi, Siti Munirah; Khamis, Shamsul; Sarbini, Shahrul Razid; Shaari, Khozirah (Malaysian Institute of Chemistry, 2022)
Morphological characteristics of Piper rubro-venosum hort. ex Rodigas bear a close resemblance to a plant identified as Piper crocatum Ruiz & Pav. in the literature. Hence, this study aimed to investigate whether both names describe the same species using data-dependent acquisition (DDA) LC-MS/MS analysis of methanol leaf extracts of P. rubro-venosum in positive and negative electrospray ionization modes. The data were analyzed using two computational mass spectrometry methods: spectral libraries search implemented in Global Natural Product Social (GNPS) molecular networking and molecular structure databases search implemented in SIRIUS. Classical molecular networking implied that the metabolites giving rise to two features with the highest intensities in the positive ionization chromatograms had distinct MS/MS spectra. De novo molecular formula annotations and machine learning predictions in SIRIUS suggested that both features were sodiated precursor ions of neolignans. Based on the accurate mass of the precursor ions, the two features were annotated as crocatin A and B, which are bicyclooctanoid neolignans previously isolated in relatively large amounts from P. crocatum leaves. Based on the findings, it can be concluded that P. crocatum and P. rubro-venosum could be two names in the literature used to refer to one species of Piper.